Determinan pengungkapan aset biologis pada perusahaan agrikultur yang terdaftar di BEI - Fitriasuri Fitriasuri; Melinda Astria Putri (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to empirically prove the effect of biological assets intensity, firm size, Ownership Concentration, type of KAP, firm growth, and profitability on the disclosure of biological assets.. This type of research  is quantitative research. The population in this study is all financial data of agricultural companies listed on the IDX in 2019-2021 as many as 26 companies. The sampling technique in this study used a purposive sampling technique for as many as 14 companies. The data analysis technique used descriptive statistical analysis, classical assumption test, multiple linear regression analysis, Coefficient of Determination, Simultaneous Test (F-Test), and Partial Test (T-Test) processed with SPSS 26. The results of this test indicate that the variable biological asset intensity and profitability have a significant positive effect on the disclosure of biological assets, and the type of KAP variable has a significant negative effect on the disclosure of biological assets. While the variables of firm size, ownership concentration, and firm growth do not affect the disclosure of biological assets.